Opposite microglial activation stages upon loss of PGRN or TREM2 result in reduced cerebral glucose metabolism. Issue 6 (23rd May 2019) - Götzl, Julia K; Brendel, Matthias; Werner, Georg; Parhizkar, Samira; Sebastian Monasor, Laura; Kleinberger, Gernot; Colombo, Alessio‐Vittorio; Deussing, Maximilian; Wagner, Matias; Winkelmann, Juliane; Diehl‐Schmid, Janine; Levin, Johannes; et al.
Abstract: Microglia adopt numerous fates with homeostatic microglia (HM) and a microglial neurodegenerative phenotype (MGnD) representing two opposite ends. A number of variants in genes selectively expressed in microglia are associated with an increased risk for neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD). Among these genes are progranulin ( GRN ) and the triggering receptor expressed on myeloid cells 2 ( TREM2 ). Both cause neurodegeneration by mechanisms involving loss of function. We have now isolated microglia from Grn −/− mice and compared their transcriptomes to those of Trem2 −/− mice . Surprisingly, while loss of Trem2 enhances the expression of genes associated with a homeostatic state, microglia derived from Grn −/− mice showed a reciprocal activation of the MGnD molecular signature and suppression of gene characteristic for HM. The opposite mRNA expression profiles are associated with divergent functional phenotypes. Although loss of TREM2 and progranulin resulted in opposite activation states and functional phenotypes of microglia, FDG (fluoro‐2‐deoxy‐d ‐glucose)‐μPET of brain revealed reduced glucose metabolism in both conditions, suggesting that opposite microglial phenotypes result in similar wide spread brain dysfunction. Synopsis: Microglia from Grn −/− & Trem2 −/− mice display opposite molecular signatures. While microglia are either locked in a hyperactivated or homeostatic state, Grn −/− & Trem2 −/− mice both show reduced glucose metabolism, suggesting that opposite microglial phenotypes result in similar brain dysfunction. First demonstration that microglia from both extremes of their functional stages cause brain wide dysfunctions. This study indicates that the therapeutic window for microglial modulation is rather narrow and care must be taken to balance microglial activity. Abstract : Microglia from Grn −/− & Trem2 −/− mice display opposite molecular signatures. While microglia are either locked in a hyperactivated or homeostatic state, Grn −/− & Trem2 −/− mice both show reduced glucose metabolism, suggesting that opposite microglial phenotypes result in similar brain dysfunction.